What the Statistical and Social Inquiry Society of Ireland has effected (1847-1880) - SSISI (Statistical and Social Inquiry Society of Ireland, 1881)
Without referring to the dissemination of sound statistical knowledge and a knowledge of Political Economy, and the correction of erroneous impressions, and the saving of waste of capital by discouraging such enterprises as the attempt to manufacture sugar from beet root in Ireland, or the attempt to grow flax in districts not suited for it, the most definite measure of what the Society has effected is the extent to which the Society has contributed to the formation of public opinion upon questions that have been actually successfully legislated upon. This is the function which such bodies as the Statistical Society and the National Association for the Promotion of Social Science have been recognized by the press as specially fitted to discharge.
Read before the Society, 30 November 1880
Keywords: Statistical and Social Inquiry Society of Ireland; Policy formation; 314.15